Kedudukan dan Tanggung Jawab Notaris Penerima Protokol Notaris yang Meninggal Dunia - Eko Permana Putra; Yuliandri Yuliandri; Azmi Fendri (Alhurriyah, 2020)
answer the needs and interests of the community of legal certainty, as stated in the agreements, agreements and agreements made by the parties in the form of authentic deeds. The making of an authentic deed as a perfect proof and no further evidence is needed to strengthen the arguments in a legal case. Authentic deed consists of minuta deed and a copy of the deed. Minutes of deed are kept by a Notary who is part of the Notary protocol which must be kept and maintained by the notary because it is a state archive. Article 1 number 8 of the UUJN states that "Authentic Deed that is kept as a notary protocol is minuta deed, that is, the original deed which includes the signatures of the registrants, witnesses, and Notary that are kept as part of the notary protocol. Notary recipient of other notary protocols obliged to save this deed is not responsible for the contents of the deed of the notary protocol that it receives. The notary is obliged directly to the Notary protocol. The death of a Notary Public, in addition to leaving problems regarding work pending, of course, will also leave other problems related to the Notary protocol. Notary recipient of the Notary protocol is not the deed maker of the Notary protocol submitted to him. The notary recipient of the protocol can provide services to the client or the public by issuing a grosse deed, a copy of the deed and a citation of the deed of minuta deed which is part of the Notary protocol that has been submitted to him.